Penerapan metode Two Stay Two Stray sebagai upaya meningkatkan pemahaman konsep globalisasi - Artiningsih, Zumi (Jurnal Kualita Pendidikan, 2024)
The purpose of this study was to improve the understanding of the concept of globalization and the quality of the PKn learning process, especially on globalization material by applying the Two Stay Two Stray method to fourth grade students of SD Negeri Tugu Lor, Karanganyar District, Demak in the 2019/2020 academic year. This research is a classroom action research carried out in three cycles consisting of planning, action, observation and reflection stages. The subjects of this study were teachers and fourth grade students of SD Negeri Tugu Lor, Karanganyar District, Demak in the 2019/2020 academic year totaling 36 students. The data collection techniques used were documentation, observation, tests and interviews. The data analysis technique used was an interactive analysis model consisting of three components, namely data reduction, data presentation, and drawing conclusions. The validity test of this study used triangulation of data sources and triangulation of data collection techniques. Based on the research results, it can be concluded that through the application of the Two Stay Two Stray method, it can improve the understanding of concepts and the quality of the PKn learning process about globalization in grade IV students of Tugu Lor Elementary School, Karanganyar District, Demak in the 2019/2020 academic year.